Motives for Cooperation in the One-Shot Prisoner's Dilemma. Issue 4 (28th November 2022) - Schneider, Mark; Shields, Timothy
Abstract: We investigate the motives for cooperation in the one-shot Prisoner's Dilemma (PD). A prior study finds that cooperation rates in one-shot PD games can be ranked empirically by the social surplus from cooperation. That study employs symmetric payoffs from cooperation in simultaneous PD games. Hence, in that setting, it is not possible to discern the motives for cooperation since three prominent social welfare criteria, social surplus (efficiency) preferences, Rawlsian maximin preferences, and inequity aversion make the same predictions. In the present paper, we conduct an experiment to identify which of these social preferences best explains differences in cooperation rates and to study the effects of the risk of non-cooperation.